Learning of uncertainty in an introductory astronomy course in remote asynchronous delivery during Covid-19 lockdown - Dehipawala, Sunil; Schanning, Ian; Tremberger, George; Cheung, Tak Choi David (International Journal of Research in STEM Education, 2021)
The teaching of an introductory astronomy course in remote delivery during Covid-19 lockdown encountered a unique issue in terms of a mixture of three student groups. They are the science majors, science-interested students, and non-science majors to satisfy science requirement in our Two-year community college located in New York City. The learning of how to assess uncertainty would be of a universal concern in the three groups. Uncertainty examples includes shoe size selection experience in daily life for non-science majors, distance measurement uncertainty for science-interested students who are parents, and simulation uncertainty for science majors. Reciting or memorizing a narrative in remote learning should be supplemented with a discussion using an alternative perspective with intellectual maturity, and the uncertainty theme would fit well for the learning of any chapters in an astronomy textbook. Assessment exercise questions are developed. The strategy to discourage rote learning and plagiarism in the remote asynchronous delivery of introductory astronomy at the college level is discussed.